1998
DOI: 10.1071/s97085
|View full text |Cite
|
Sign up to set email alerts
|

Sorption and desorption of cadmium from some New Zealand soils: effect of pH and contact time

Abstract: The effects of soil pH on the desorption of native soil cadmium (Cd), and on the sorption and desorption of added Cd at low concentrations, have been examined for 6 New Zealand soils ranging from pH 4·9 to 6·2. The effect of contact time with added Cd on subsequent desorption from soil has also been studied. Cadmium desorption was determined by repeated equilibrations in 0·01 М Ca(NO3)2 solution. Cadmium sorption ranged between 38% and 96% from an initial addition of 2 µg Cd/g soil. The effect of increasing so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
55
0
11

Year Published

1999
1999
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 120 publications
(71 citation statements)
references
References 0 publications
5
55
0
11
Order By: Relevance
“…For Heilongjiang, Zhejiang and Guangdong soils, in the presence of citric, malic and tartaric acids, desorption of REEs decreased with increasing pH values, so it did for Jiangxi soil in the presence of NO À 3 , acetic acid and tartaric acid. A similar phenomenon was also reported for other metal ions such as Cu 2þ (Padmanabham, 1983), Cd 2þ (Gray et al, 1998) and Zn 2þ (Pardo and Guadalix, 1996). It is generally recognized that pH can affect desorption of heavy metal from two aspects.…”
Section: Effect Of Organic Ligands and Ph On Extractable Rees From Soilssupporting
confidence: 77%
“…For Heilongjiang, Zhejiang and Guangdong soils, in the presence of citric, malic and tartaric acids, desorption of REEs decreased with increasing pH values, so it did for Jiangxi soil in the presence of NO À 3 , acetic acid and tartaric acid. A similar phenomenon was also reported for other metal ions such as Cu 2þ (Padmanabham, 1983), Cd 2þ (Gray et al, 1998) and Zn 2þ (Pardo and Guadalix, 1996). It is generally recognized that pH can affect desorption of heavy metal from two aspects.…”
Section: Effect Of Organic Ligands and Ph On Extractable Rees From Soilssupporting
confidence: 77%
“…As soil pH increases, sorption of Cd onto soil components, i.e., clay, organic matter and soil oxides also increases. There is also an accompanying decrease in desorption of Cd from these components into soil solution with increasing soil pH as previously demonstrated (Gray et al 1998). Therefore, increasing soil pH leads to a reduction of Cd in soil solution, the Cd pool in soils most readily available for plant uptake.…”
Section: Plant CD Concentrationsmentioning
confidence: 48%
“…The results of several previous studies have also identified soil pH as an important soil property controlling sorption/desorption and solubility of native and added soil Cd (Salam & Helmke 1998;Gray et al 1998Gray et al , 1999, and therefore likely to play an important role influencing Cd phytoavailability. As a soil property that is relatively easy to manipulate, soil pH may be important in the management and control of plant Cd concentrations.…”
Section: Introductionmentioning
confidence: 82%
“…A Cd %ads foi, em média, de 27, 35 e 55 %, para pH 4,5; 5,5; e 6,5, respectivamente. A importância do pH como fatorchave em controlar a adsorção de Cd tem sido demonstrada em vários trabalhos (Naidu et al, 1994;Gray et al, 1998Gray et al, , 1999Krishnamurti & Naidu, 2003). Os dados obtidos neste trabalho estão de acordo com relatos prévios da literatura, segundo os quais o aumento do pH do solo resulta em um aumento da capacidade adsortiva dos mesmos (Alloway, 1990;Kabata-Pendias & Pendias, 2001;Dias et al, 2001).…”
Section: Resultsunclassified
“…É amplamente relatado na literatura que os processos de adsorção de elementos-traço não são completamente reversíveis. Explicações para esse fato incluem: difusão dos elementos para o interior das partículas ou microporos dos óxidos (Backes et al, 1995;Gray et al, 1998); precipitação (Farrah & Pickering, 1978); incorporação na estrutura cristalina dos óxidos (Ainsworth et al, 1994) e readsorção ao adsorvente (Davis & Upadhyaya, 1996).…”
Section: Resíduos Padronizadosunclassified